Two new Tegenaria species (Araneae: Agelenidae) from Portugal - Bolzern, Angelo; Crespo, Luís; Cardoso, Pedro (Zootaxa, 2009)
The genera complex Tegenaria/Malthonica is a problematic spider group of the family Agelenidae. Besides taxonomical problems, new European species are described on a regular basis. Here two species from Portugal, Tegenaria barrientosi sp. n. and Tegenaria incognita sp. n., are described. Both species show a significant similarity to T. bucculenta, T. feminea and T. montigena, a species group restricted to the Iberian Peninsula. T. barrientosi sp. n. can be separated by the pyramidal shaped ventral branch of the conductor, the shape and arrangement of the RTA and the proportion of the bulblength to the cymbium-length, the run and shortness of the copulatory ducts with the diverticulae originating laterally and the irregularly sclerotized egg-shaped spermathecae, which are touching each other anteriorly. T. incognita sp. n. can be separated by the very broad lateral branch and the almost completely hidden lateroventral branch of the RTA, the shape of the conductor with the terminal end pointing towards posterior, the inwards directed epigynal teeth, the run and shortness of the copulatory ducts with the anteriorly originating diverticulae.